Effect on health-related quality of life of the X-Bolt dynamic plating system versus the sliding hip screw for the fixation of trochanteric fractures of the hip in adults: the WHiTE Four randomized clinical trial. (1st February 2021) - Griffin, Xavier L.; Achten, Juul; O'Connor, Heather Marie; Cook, Jonathan A.; Costa, Matt L.
Abstract : Aims: Surgical treatment of hip fracture is challenging; the bone is porotic and fixation failure can be catastrophic. Novel implants are available which may yield superior clinical outcomes. This study compared the clinical effectiveness of the novel X-Bolt Hip System (XHS) with the sliding hip screw (SHS) for the treatment of fragility hip fractures. Methods: We conducted a multicentre, superiority, randomized controlled trial. Patients aged 60 years and older with a trochanteric hip fracture were recruited in ten acute UK NHS hospitals. Participants were randomly allocated to fixation of their fracture with XHS or SHS. A total of 1, 128 participants were randomized with 564 participants allocated to each group. Participants and outcome assessors were blind to treatment allocation. The primary outcome was the EuroQol five-dimension five-level health status (EQ-5D-5L) utility at four months. The minimum clinically important difference in utility was pre-specified at 0.075. Secondary outcomes were EQ-5D-5L utility at 12 months, mortality, residential status, mobility, revision surgery, and radiological measures. Results: Overall, 437 and 443 participants were analyzed in the primary intention-to-treat analysis in XHS and SHS treatment groups respectively. There was a mean difference of 0.029 in adjusted utility index in favour of XHS with no evidence of a difference between treatment groups (95% confidence interval -0.013 to 0.070; p = 0.175). There was no evidence of any differences between treatment groups in any of the secondary outcomes. The pattern and overall risk of adverse events associated with both treatments was similar. Conclusion: Any difference in four-month health-related quality of life between the XHS and SHS is small and not clinically important. There was no evidence of a difference in the safety profile of the two treatments; both were associated with lower risks of revision surgery than previously reported. Cite this article: Bone Joint J 2021;103-B(2):256–263.